Analysis of Creative Thinking Ability in View of Learning Style in Class IV Elementary School Science Learning - Ica, Eni Elmawati; Wijaya, Andika Kusuna; Utama, Erdi Guna (STKIP Singkawang, 2024)
This research aims to describe students' creative thinking abilities in terms of learning styles and to describe the factors that influence creative thinking abilities in terms of learning styles in the science material on changes in the shape of objects in class IV. This research method is qualitative descriptive research. The subjects in this research were all class IV of SDN 88 Singkawang which consisted of creative thinking abilities in terms of learning style, namely students with a visual learning style were able to carry out all indicators well and had an average of 63.04 with medium criteria, students with an auditory learning style able to carry out all indicators well and have an average of 54.34 with low criteria, students with a reading learning style are able to carry out all indicators well and have an average of 55.43 with low criteria, students with a kinesthetic learning style are able to carry out all indicators well and has an average of 76.80 with high criteria. The data collection technique used is. The data analysis technique consists of stages of data reduction, data presentation, and drawing conclusions. From the research results it can be concluded that: students with high creative thinking abilities have a kinesthetic learning style, students with moderate creative thinking abilities have a moderate learning style, have a visual learning style, students with low creative thinking abilities have an auditory and reading learning style.